Penggunaan Media Gambar Berseri dalam Mengembangkan Keterampilan Berbicara di Taman Kanak-Kanak - Ranggayoni, Russy (Jumper: Journal of Educational Multidisciplinary Research, 2024)
This research aims to find out how the use of serial image media develops speaking skills at the Mekar Sari Private Kindergarten. The research method used in this research is classroom action research. The subjects of this research were children aged 4 - 5 years (Group A) in the Mekar Sari Private Kindergarten, totaling 14 children. Data collection techniques in this research used observation, interviews and documentation. The research results show that the use of serial image media in developing children's speaking skills is very effective. This was proven in the pre-cycle activities, there were no children who developed according to expectations and developed very well, in Cycle I the children who had not yet developed (BB) were 13% and were starting to develop (MB) 53%, while those who developed according to expectations (BSH) were 27%. and 7% very well developed (BSB). In the second cycle there was a significant increase, namely developing very well (BSB) 53% and developing according to expectations (BSH) 40%, starting to develop (MB) 7% and there were no more children who had not yet developed (BB).